Organización social-comunitaria e inseguridad ciudadana en el barrio La Octubrina de la ciudad de El Guabo. - Gallegos Macas, Leidy Emperatriz (My University, 2019)
The present research work on social-community organization carried out in the neighborhood La Octubrina of the city of the Guabo, focuses on citizen participation and community organization where the must interact strategically, because they pursue common goals in planning and leadership, while the inhabitants have the responsibility to protect, conserve and support the management of the infrastructure to achieve integral development, as well as to protect individual and collective assets. The general objective is framed in determining the etiological factors that affect the social organization and prevents the creation of security environments for the protection of the material and immaterial goods of the population. The epistemological reference that was used in the research is aimed at the empirical-inductive, with a mixed methodology where this methodological process allows the description and analysis of the problems that affect the place, in addition, the technique of the survey and the interview was used, and in this way to relate to the investigation. Among the results found is the bad disorganization on the part of the neighborhood council and the authorities involved such as the Municipal GAD and the Police Units. That is why citizen security strategies are established, such as: neighborhood conferences for good community living, strengthening of Community Policing Units, training the population in prevention and intervention actions aimed at maintaining citizen security and the creation of Neighborhood Brigades for Public Safety as a support mechanism.
El presente trabajo de investigación sobre la organización social-comunitaria realizada en el barrio La Octubrina de la ciudad de El Guabo, se centra en la participación ciudadana y la organización comunitaria, en donde deben interactuar estratégicamente, debido a que persiguen fines comunes a la planificación y liderazgo, mientras que a los habitantes les compete proteger, conservar y apoyar la gestión de la infraestructura tanto para alcanzar el desarrollo integral, como también para proteger los bienes individuales y colectivos. El objetivo general se enmarca en determinar los factores etiológicos que afectan a la organización social e impide la generación de ambientes de seguridad para la protección de los bienes materiales e inmateriales de la población. El referente epistemológico que se utilizó en la investigación se apunta al empírico-inductivo, con una metodología mixta en donde este proceso metodológico permite la descripción y análisis de los problemas que afectan en el lugar, además se utilizó la técnica de la encuesta y la entrevista, y de esta manera relacionar con la investigación. Entre los resultados encontrados se evidencia la mala desorganización por parte del consejo barrial y las autoridades involucradas como es el GAD Municipal y las Unidades de Policías. Por eso se establecen estrategias de seguridad ciudadana tales como: conferencias barriales para el buen vivir comunitario, fortalecimiento de las Unidades de Policía Comunitaria, capacitación a la población en acciones de prevención e intervención orientadas al mantenimiento de la seguridad ciudadana, y la conformación de Brigadas Barriales de Seguridad Ciudadana como mecanismo de apoyo.
Keywords: ORGANIZACION; COMUNITARIA; SEGURIDAD; CIUDADANA